Follow the track, all the way back - Knapman, Timothy (London Walker Books, 2018)
Little Train happily ventures out on the railroad track alone for the first time, but when he reaches the end of the tracks, it is getting dark and Little Train is worried until he recalls what his parents said about finding his way home
English Stories
1
Keywords: Locomotives -- Pictorial works -- Juvenile fiction; Locomotives; Railroad travel -- Pictorial works -- Juvenile fiction